DAMPAK KEBERADAAN RITEL MODERN TERHADAP PEREKONOMIAN PASAR TRADISIONAL DI ACEH BARAT DAN NAGAN RAYA - M. Aditya Ananda (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2019)
This paper examines the roles of modern retail businesses in the region's growth. This impact can be seen in traditional markets in western Aceh and Nagan Raya. The study population was in the districts of Aceh Barat and Nagan Raya, with a sample of all subdistricts in the district. Each district has a traditional market and retail business that has been established. The data collection techniques used by the author are conducting documentation studies, observations and interviews with the government that provides business licenses and traditional market protection. Then do a case study with secondary data sources from websites or the internet. The results of the assessment that we found in the GRDP in the districts of Aceh Barat and Nagan Raya Associated with trade businesses such as modern retail outlets also contribute to labor funding. Significant developments in the workforce occurred in 2014 from 2531 to 6475 in 2015. The conclusion based on the data above is that modern retail and traditional markets contribute to the Increased Workforce in West Aceh District. However, the development of trade in regencies in West Aceh is not enough to boost economic growth in 2016. Based on this data, it can be concluded that modern retail and traditional markets are crucial for economic growth in West Aceh District, where the trade business is the second largest business field in contributing to contribute to the West Aceh Regency GRDP.